“It is as if you were taking a shot in the dark”: Experiencing ambiguity in the pharmacological treatment of rheumatoid arthritis (Research, Society and Development, 2021)
Rheumatoid arthritis (RA) is a chronic disease that compromises patients’ quality of life and it demands an indispensable and complex pharmacological treatment. The aim of the present study was to understand patients’ experiences with the pharmacological treatment of RA. In order to explore this area, interviews were conducted with patients with RA followed at an outpatient clinic. Merleau-Ponty’s theoretical framework was applied to understand the investigated phenomenon by using the essential structures of the experience (time, space, relationships with other people, and sexuality, all of which are anchored in the body). These were used to describe the central meanings of the patients’ medication experience. The data showed that patients experienced ambiguity during the RA treatment and that it pervaded all the essential structures of the experience. The experiences that emerged from data analysis were: “waiting for the proper treatment”; “hoping for its effectiveness and safety”; “rediscovering spaces lost because of the disease”; and “self-management in controlling symptoms”. Understanding these experiences allows for the healthcare team to offer more comprehensive, holistic and effective care, contributing to better health outcomes.